2022
DOI: 10.21203/rs.3.rs-1280111/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meniscal Preservation is More Likely When Performed with Acute Anterior Cruciate Ligament Repair Rather Than with Anterior Cruciate Ligament Reconstruction

Abstract: BackgroundRupture of the anterior cruciate ligament (ACL) often occurs in conjunction with meniscal tears. In this study we investigate the rates and outcomes of meniscal repair surgery performed with ACL reconstruction compared with acute ACL repair surgery.MethodsData was collected for all patients undergoing surgery for ACL ruptures between 2012 and 2018, including ACL reconstruction with hamstring autograft and primary ACL repair augmented with suture tape. Patients undergoing multiligament surgery was exc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Also, Endo Button is less expensive, and, in case of repair failure, ACLR would be easier to perform. However, both anchor and Endo Button have a major potential disadvantage in the form of postoperative displacement [17].A new study reported that ACL repair (suture anchor) was associated with greater meniscal preservation compared to ACLR[18]. In our study, seven patients had concomitant medial meniscus injury, but we did not assess the rate of repair of medial meniscus in them, and this was beyond the scope of the present study.According to a recent cadaveric study, in a femoral avulsion model, valgus, varus, internal, or external rotation of knees that underwent ACL augmentation repair (internal brace) are similar to those thatJournal of Community Medicine and Public Health Reports ISSN: 2692-9899 Citation: Qalib YO, Dachepalli S, Medagam SR, Gupta LK (2024) Suture Tape Augmentation Repair For Partial Acl Tears: A Prospective Case Series And Surgical Technique.…”
mentioning
confidence: 86%
“…Also, Endo Button is less expensive, and, in case of repair failure, ACLR would be easier to perform. However, both anchor and Endo Button have a major potential disadvantage in the form of postoperative displacement [17].A new study reported that ACL repair (suture anchor) was associated with greater meniscal preservation compared to ACLR[18]. In our study, seven patients had concomitant medial meniscus injury, but we did not assess the rate of repair of medial meniscus in them, and this was beyond the scope of the present study.According to a recent cadaveric study, in a femoral avulsion model, valgus, varus, internal, or external rotation of knees that underwent ACL augmentation repair (internal brace) are similar to those thatJournal of Community Medicine and Public Health Reports ISSN: 2692-9899 Citation: Qalib YO, Dachepalli S, Medagam SR, Gupta LK (2024) Suture Tape Augmentation Repair For Partial Acl Tears: A Prospective Case Series And Surgical Technique.…”
mentioning
confidence: 86%